Foreign Acquisition and the Performance of New Zealand Firms - Richard Fabling; Lynda Sanderson (New Zealand Government, The Treasury, 2011)
This paper examines the firm-level determinants of foreign acquisitions of New Zealand companies, and the consequences for both the purchased firms and the workers within those firms. We follow a combined propensity score matching and difference-in- differences approach to identify and address endogenous selection of acquisition targets. The results suggest that foreign firms tend to target high-performing New Zealand companies. Acquired firms then exhibit higher growth in average wages and output, relative to similar domestic firms, but do not appear in general to increase their productivity or capital intensity. We find no evidence of differential survival rates for recently acquired foreign firms.
Keywords: D22; F23; 330; Firm performance; foreign direct investment (FDI); Auslandsinvestition; Ausländisch; Unternehmenserfolg; Neuseeland